Pendekatan Konseling Individu Berbasis Spiritualitas Kesabaran dalam Tafsir Ibnu Katsir atas QS Al-Baqarah:153 - Adeko, Uun; Ristianti, Dina Hajja; Sumarto, Sumarto; Ridwan, Rifanto bin; Kholilah, Emmi; Mukhlishah, Mukhlishah (Edumulti: Jurnal Rumpun Ilmu Pendidikan Multidisiplin, 2025)
This study aims to explore an individual counseling approach based on spiritual patience in the perspective of QS interpretation. Al-Baqarah verse 153 according to Ibn Kathir, as well as its relevance for students who face various psychological problems in the school environment. The research method uses a qualitative approach with a type of field research at SMKN 4 Kepahiang, Bengkulu Province. The research subjects involved students who experienced academic, behavioral, social, and emotional problems. Data was collected through in-depth interviews and analyzed with qualitative descriptive techniques. The results of the study show that understanding patience as a determination in facing life's tests, accompanied by regular prayer practices, can help students manage stress, increase learning motivation, and improve worship habits. This counseling approach includes the stages of problem identification, patient meaning, spiritual strengthening, action planning, and evaluation. The application of spiritual patience-based counseling has been proven effective in building students' psychological and spiritual resilience. In addition, this approach strengthens optimism, increases confidence, and makes a positive contribution to students' readiness to face various life challenges.